Evaluation Situations, Stakeholders & Strategies - Glenn Israel; David Diehl; Sebastian Galindo-Gonzalez (EDIS)
WC090, a 4-page illustrated fact sheet by Glenn Israel, David Diehl, and Sebastian Galindo-Gonzalez, provides guidelines for extension faculty to tailor their evaluation activities to balance their available time and resources with the situation, as well as their individual and stakeholders’ needs. Includes references. Published by the UF Department of Agricultural Education and Communication, November 2009.